2017
DOI: 10.1186/s12879-017-2873-z
|View full text |Cite
|
Sign up to set email alerts
|

Update of incidence and antimicrobial susceptibility trends of Escherichia coli and Klebsiella pneumoniae isolates from Chinese intra-abdominal infection patients

Abstract: BackgroundTo evaluate in vitro susceptibilities of aerobic and facultative Gram-negative bacterial (GNB) isolates from intra-abdominal infections (IAIs) to 12 selected antimicrobials in Chinese hospitals from 2012 to 2014.MethodsHospital acquired (HA) and community acquired (CA) IAIs were collected from 21 centers in 16 Chinese cities. Extended spectrum beta-lactamase (ESBL) status and antimicrobial susceptibilities were determined at a central laboratory using CLSI broth microdilution and interpretive standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
4
21
1
1
Order By: Relevance
“…SMART is a global multi-center abdominal infection program that mainly monitors Gram-negative bacteria and their susceptibility to antibiotics. The data showed that Enterobacteriaceae were still the major strains found in abdominal infections (2010–2014) in China, the most common types being E. coli and K. pneumoniae , which is in agreement with a previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…SMART is a global multi-center abdominal infection program that mainly monitors Gram-negative bacteria and their susceptibility to antibiotics. The data showed that Enterobacteriaceae were still the major strains found in abdominal infections (2010–2014) in China, the most common types being E. coli and K. pneumoniae , which is in agreement with a previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…coli ST131 isolates showed high antimicrobial resistance to SXT, CIP, LEV, and CTX. In China, sulfonamides (such as SXT), β-lactams (such as CTX), and quinolones (such as CIP) are often used to cure E. coli infections; therefore, the high resistance of E. coli ST131 may be due to the frequent and inappropriate use of these antimicrobials [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Both E. coli and E. cloacae producing ESBLs are closely related to the drug resistance of antibiotics, and the same type of bacteria are likely to carry a variety of ESBLs, leading to multi-drug resistance [17,18]. Studies have also shown that there are multiple drug resistance mechanisms in E. coli and E. cloacae, which include mutations in Amp C enzymes and porin loss, which has been described in previous literatures [19,20]. However, we did not explore molucular mechanisms of resistances.…”
Section: Discussionmentioning
confidence: 79%